Social Vulnerability among Foreign-Born Pregnant Women and Maternal Virologic Control of HIV - Premkumar, Ashish; Yee, Lynn M.; Benes, Lia; Miller, Emily S. (American Journal of Perinatology, 2020)
Objective The aim of this study was to assess whether social vulnerability among foreign-born pregnant women living with HIV is associated with maternal viremia during pregnancy.Study Design This retrospective cohort study included all foreign-born pregnant women living with HIV who received prenatal care in a multidisciplinary prenatal clinic between 2009 and 2018. A licensed clinical social worker evaluated all women and kept detailed clinical records on immigration status and social support. Social vulnerability was defined as both living in the United States for less than 5 years and reporting no family or friends for support. The primary outcome was evidence of viral non-suppression after achievement of initial suppression. Secondary outcomes were the proportion of women who required > 12 weeks after starting antiretroviral therapy to achieve viral suppression, median time to first viral suppression (in weeks) after initiation of antiretroviral therapy, and the proportion who missed ≥ 5 doses of antiretroviral therapy. Bivariable analyses were performed.Results A total of 111 foreign-born women were eligible for analysis, of whom 25 (23%) were classified as socially vulnerable. Social and clinical characteristics of women diverged by social vulnerability categorization but no differences reached statistical significance. On bivariable analysis, socially-vulnerable women were at increased risk for needing > 12 weeks to achieve viral suppression (relative risk: 1.78, 95% confidence interval: 1.18–2.67), though there was no association with missing ≥ 5 doses of antiretroviral therapy or median time to viral suppression after initiation of antiretroviral therapy.Conclusion Among foreign-born, pregnant women living with HIV, markers of virologic control during pregnancy were noted to be worse among socially-vulnerable women. Insofar as maternal viremia is the predominant driver of perinatal transmission, closer clinical surveillance and support may be indicated in this population.Key Points
Keywords: social vulnerability; social determinants of health; HIV; mother-to-child transmission